2018
DOI: 10.1111/ajad.12660
|View full text |Cite
|
Sign up to set email alerts
|

Abstinence and reduced frequency of use are associated with improvements in quality of life among treatment‐seekers with cannabis use disorder

Abstract: Background And Objective Many patients with cannabis use disorder (CUD) do not achieve or do not have abstinence as a goal of treatment, rather they reduce their use. Assessing outcome measures as they relate to functioning and reductions in cannabis use is an important area of study. Quality of life (QoL) shows promise as one such measure. Past studies have demonstrated gender differences in QoL and CUD. We aim to assess (1) the relationship between cannabis use and QoL and (2) gender effects in an outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Study findings are consistent with prior studies demonstrating improvements in depression, anxiety and sleep in individuals with CUD who reduced use over time (Hser et al 2017), and with improvements in quality of life in treatment-seeking individuals with CUD who reduced or abstained from use (Brezing et al 2018). Though many individuals report using cannabis to help with insomnia, and cannabis use has been associated with improvements in short-term sleep outcomes (National Academies of Science, Engineering and Medicine 2017), heavy, prolonged cannabis use may have more detrimental effects on sleep quality, particularly during withdrawal which typically subsides within 2 weeks after cessation of use (Budney et al 2003).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Study findings are consistent with prior studies demonstrating improvements in depression, anxiety and sleep in individuals with CUD who reduced use over time (Hser et al 2017), and with improvements in quality of life in treatment-seeking individuals with CUD who reduced or abstained from use (Brezing et al 2018). Though many individuals report using cannabis to help with insomnia, and cannabis use has been associated with improvements in short-term sleep outcomes (National Academies of Science, Engineering and Medicine 2017), heavy, prolonged cannabis use may have more detrimental effects on sleep quality, particularly during withdrawal which typically subsides within 2 weeks after cessation of use (Budney et al 2003).…”
Section: Discussionsupporting
confidence: 89%
“…Few studies have directly examined functional improvements associated with cannabis use reduction, but recent work suggests improvements in quality of life with abstinence and lower use frequency (Brezing et al. 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the What is Recovery Study, AOD abstinence (vs. any substance use) was strongly and uniquely related to greater quality of life (Subbaraman & Witbrodt, 2014). Similar correlations have also been observed for recovery capital (Laudet & White, 2008;Sinclair et al, 2021), quality of life (Brezing et al, 2018), and psychological distress (Erga et al, 2021). Our study replicates and extends these findings to the broader population of individuals who have resolved an AOD problem, regardless of treatment seeking status, primary substance used, and recovery duration/identity.…”
Section: Associations Between Substance Use Status and Current Indice...mentioning
confidence: 57%
“…Previous cannabis studies have operationalized reduction outcomes as a proportion of days used (Brezing et al, 2018; Lintzeris et al, 2019), grams used per day (Tomko et al, 2018), and decreasing trajectory of use (i.e., negative slope; Hser et al, 2017), but have demonstrated an inconsistent association between reduction and improved psychosocial functioning (Brezing et al, 2018; Hser et al, 2017; Lintzeris et al, 2019). In a pharmacotherapy trial for CUD, reduction in self-reported days of use was associated with improved quality of life, but the reduction in grams of cannabis used was not (Brezing et al, 2018). Another trial found the reduction in days of use was associated with improvements in depression and anxiety, but not quality of life (Hser et al, 2017).…”
mentioning
confidence: 99%